Discourse-related features and functional projections - Cruschina, Silvio (Oxford : Oxford University Press, 2012)
Silvio Cruschina uses a comparative analysis to determine the syntax of the functional projections associated with discourse-related features, and to account for the marked word orders found in Romance, particularly in the fronting phenomena.
Description based on online resource; title from PDF title page (viewed on Apr. 19, 2012).
Includes bibliographical references and index.
Keywords: Grammar, Comparative and general -- Syntax; Functionalism (Linguistics); Discourse analysis